STUDI LITERATUR: FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN ALAT PELINDUNG DIRI (APD) DI SEKTOR KONSTRUKSI - Alya Alfianti Balqis; Intan Andhani; Raduwi Wahyuni; Abdurrozzaq Hasibuan (CV. Adiba Aisha Amira, 2025)
Background: The construction industry is a sector with a high risk of work accidents, so the use of Personal Protective Equipment (PPE) is an important aspect in ensuring worker safety. However, worker compliance with the use of PPE is still low due to various factors such as knowledge, attitudes, availability of PPE, and work safety culture. Objective: This study aims to identify and analyze factors that influence compliance with the use of Personal Protective Equipment (PPE) among construction workers. Method: This article uses a literature study method by examining scientific articles indexed by Google Scholar in 2018–2024 which discuss factors that influence compliance with the use of PPE among construction workers. Results: The results of the literature study show that construction workers' compliance in using Personal Protective Equipment (PPE) is influenced by internal factors such as knowledge, attitudes, motivation and work experience, as well as external factors such as supervision, availability of PPE, company policies and social support. These factors interact with each other to form a work safety culture in the construction project environment. Conclusion: Compliance with the use of PPE in the construction sector requires a comprehensive approach that includes education, fostering work culture, and consistent implementation of safety policies.